Antitumour, acute toxicity and molecular modeling studies of 4-(pyridin-4-yl)-6-(thiophen-2-yl) pyrimidin-2(1H)-one against Ehrlich ascites carcinoma and sarcoma-180. Issue 6 (June 2018) - Kumar, Dinesh; Sharma, Pooja; Nepali, Kunal; Mahajan, Girish; Mintoo, Mubashir J.; Singh, Amarinder; Singh, Gurpreet; Mondhe, Dilip M.; Singh, Gurdarshan; Jain, Subheet K.; Gupta, Girish K.; Ntie-Kang, Fidele
Abstract: In an effort to discover an effective and selective antitumour agent, synthesis and anti-cancer potential of 4-(pyridin-4-yl)-6-(thiophen-2-yl) pyrimidin-2(1 H )-one (SK-25 ), which has been reported earlier by us with significant cytotoxicity towards MiaPaCa-2 malignant cells, with an IC50 value of 1.95 μM and was found to instigate apoptosis. In the present study, the antitumour efficacy ofSK-25 was investigated on Ehrlich ascites tumour (EAT, solid), Sarcoma 180 (solid) tumour and Ehrlich ascites carcinoma. The compound was found to inhibit tumour development by 94.71% in Ehrlich ascites carcinoma (EAC), 59.06% in Ehrlich tumour (ET, solid) and 45.68% in Sarcoma-180 (solid) at 30 mg/kg dose. Additionally, SK-25 was established to be non-toxic at a maximum tolerated dose of 1000 mg/kg in acute oral toxicity in Swiss-albino mice. Computer-based predictions also show that the compounds could have an interesting DMPK profile since all 51 computed physicochemical parameters fall within the recommended range for 95% of known drugs. The current study provides insight for further investigation of the antitumour potential of the molecule.